Policy Implications of Road Accident Patterns in Pakistan - Badar, Aiman (Journal of Professional Research in Social Sciences, 2024)
There is a serious threat to public health and safety from road accidents in Pakistan. The people, places, and things that play a role in these incidents were the focus of this investigation. This descriptive study makes use of a secondary source data set that relates to RTCs that occurred on highways and motorways in Pakistan from 2016 to 2021. Based on our research, heavy traffic times, weekends, and populated areas were found to be high-risk places and times. Accident causes include unfavorable weather, drivers’ ages and genders, and the condition of the roads. The 5Ps of road safety: plan, protect, prevent, prepare, and promote propose a holistic strategy to tackle these problems. Pakistan may drastically cut down on traffic accidents and increase safety by adopting these measures. <!–a=1–>